A review on the effects of inter-firm technology transfer characteristics and degree of technology transfer - Che Rose, Raduan; Uli, Jegak; Naresh, Kumar; Abdul Wahab, Sazali (Eurojournals, 2009)
The inter-firm technology transfer (TT) through joint ventures (JVs) shaped between foreign multinational corporations (MNCs) and local companies have increasingly emerged as an efficient formal mechanism to internalize foreign technologies, knowledge and competencies. Although the TT processes are complex and difficult, collaborative JVs are seen as the appropriate strategy to extract tacit and explicit knowledge in enhancing the local companies’ competitiveness, indigenous technical capability, technological development, and potentials for local innovation. Since JVs are frequently perceived as instable organizations and technologies are the main source of competitive advantage of the MNCs, transferring technology thus involves various facilitators, actors and complicated relationship between partners which could directly affect the degree of technologies transferred to local companies. Building on the integrated knowledge-based view and organizational learning perspective, and previous TT models this article advances a holistic TT model in conceptualizing the relative relationships and effects of technology transfer characteristics (TTCHARS) and its dimensions on degree of technology transfer (TTDEG).